Why Can We See Things? - Kayoko Nohara; Betti Marenko (DIID)
This article proposes that key approaches from Translation Studies offer a useful springboard for reflecting on the theme of Design and Unknowns. Presenting a range of working definitions, it frames translation as a generative, creative, and transformative process — a tool for thinking about encounters with otherness, the unknown, and the unknowable. The article focuses on the translation strategies of domestication and foreignization as different ways of engaging with cultural idiosyncrasies. These strategies are illustrated through visual examples from the translation of school science textbooks in post-war Japan, showing how translation shaped narratives around science literacy. It concludes by exploring the notion of untranslatability, highlighting how the creative gap of not-knowing within translation can represent an ethic of engagement with the unknown.